Aqueous dispersions of oleic acid nanodroplets for thymol encapsulation - Gutiérrez González, Paula (2024)
This study focuses on the use of oleic acid to disperse thymol as nanodroplets, stabilized by a mixture of alkylpolyglucoside and lecithin, in an aqueous environment. This approach aims to develop innovative platforms for the encapsulation and release of poorly water-soluble molecules such as thymol, useful for drug delivery and insecticide systems. The results highlight the critical role of controlling the content and concentration of the oil phase (thymol-oleic acid mixture) in achieving optimal thymol dispersion and nanodispersion stability. The interplay between the ability of oleic acid to inhibit thymol crystallization and the maximum dispersible oil amount is crucial. It affects the dispersion of thymol within the nanodroplets and influences coalescence and Ostwald ripening phenomena. The balance between oleic acid and thymol content is key: while oleic acid stabilizes dispersions, higher thymol content increases droplet size, potentially triggering destabilization. The uneven distribution of thymol within the droplets, revealed by fluorescence spectroscopy, suggests that up to three different chemical environments exist. This investigation may pave the way for the development of efficient platforms to improve access to biologically relevant, poorly soluble molecules.